RF behavior of undoped channel ultra-thin body with ultra-thin BOX MOSFETs - Mohd Khairuddin, Md Arshad, Dr.; Mostafa, Emam; Kilchytska, Valeria I., Dr.; Andrieu, François, Dr.; Flandre, Denis, Prof.; Raskin, Jean-Pierre P., Prof. (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org/